Chitosan 2% Effect on Prohibiting the Growth of Candida Albicans on Heatcured Acrylic Resin - Angela Evelyna; Dahlia Sutanto; Elizabeth Tiffany (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2017)
Maintaining acrylic denture hygiene is a necessary to prohibit the growth of several oral fungi such as Candida albicans. Candida albicans are the main etiological microorganism of denture stomatitis. One of the ways to clean denture is by immersion on synthetic denture cleaner liquid such as oxygenizing denture cleaners. However, synthetic denture cleaner have several limitation due to its biocompatibility on human body especially oral tissue. Chitosan is a derivate of chitin, a natural compound of sea creature exosceleton. Chitosan have antifungi and antibacterial nature. The objective of this study is to evaluate the antifungi efectifity of chitosan 2% on acrylic heatcured and compare it with oxygenizing denture cleaner. Aquades is used as a control. The sample consists of 15 acrylic heatcured bars (10x10x2 mm) prepared by contamination on Candida albicans suspensions at temperature 37°C for 24 hours and immersed on 3 different treatments wich are chitosan 2%, oxygenizing denture cleanser, and aquades as control and then, the solutions are being vibrate and put into sabouraud dextrose agar medium. The colony of Candida albicans counted manually. Result shows, highest mean of Candida albicans colony on aquades group (365,66 CFU/plate), followed by oxygenizing denture cleanser treatment (178,33 CFU/plate). The smallest number colony of Candida albicans are found at chitosan 2% treatment (45,33 CFU/plate). Statistical analysis using ANOVA one way shows F=9.826 and p=0, this means, there is minimal one pair of groups with very significant differential (p<0,01) which are chitosan 2% and oxygenizing denture cleanser compared to aquades as control. The difference between those two treatments also significant. Conclusions of this study is that chitosan 2% solution have a sifnificant effect on prohibiting the growth of Candida albicans colony on acrylic heatcured denture base materials. The effectivity of this solution is significantly higher than oxygenizing denture cleanser treatment.